2014
DOI: 10.1186/1749-7922-9-51
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative management attempted for selective high grade blunt hepatosplenic trauma is a feasible strategy

Abstract: BackgroundThere is growing evidence of clinical data recently for successful outcomes of non-operative management (NOM) for blunt hepatic and spleen injuries (BHSI). However, the effectiveness of NOM for high-grade BHSI remains undefined. The aim of the present study was to review our experience with NOM in high-grade BHSI and compare results with the existing related data worldwide.MethodsIn this retrospectively protocol-driven study, 150 patients with grade 3–5 BHSI were enrolled during a 3-year period. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 33 publications
3
30
0
1
Order By: Relevance
“…16 Study from Hsieh et al, Carillo et al, suggested that increasing need of blood transfusion was also a sign to manage the patient operatively. 2,18 It is in accordance with our study that blood transfusion is also a predictor failure in managing blunt liver trauma conservatively.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…16 Study from Hsieh et al, Carillo et al, suggested that increasing need of blood transfusion was also a sign to manage the patient operatively. 2,18 It is in accordance with our study that blood transfusion is also a predictor failure in managing blunt liver trauma conservatively.…”
Section: Discussionsupporting
confidence: 77%
“…The advantages of NOM include lower hospital cost, earlier discharge, avoiding unnecessary laparotomy, fewer abdominal complication and reduced number of blood transfusion. 1,14,17 Most prior studies concluded that the main reason for the failure of NOM is the hemodynamic instability, whereas this observation was contradicted by Mitsusada et al 18,19 Various predictors of NOM failure have been documented in the literatures. [20][21][22][23][24][25][26][27][28][29] Literature review of Bhangu et al, reported AAST grades 4-5, the presence of moderate or large hemoperitoneum, increasing ISS and increasing age were significantly associated with increased risk factor of NOM failure in blunt liver injuries.…”
Section: Discussionmentioning
confidence: 77%
“…Boyuk et al (10) proposed that the failure rate is higher in patients who received more than 2 IU of RBC. Hsieh et al (17) reported that patients with a low hemoglobin level at admission and a high number of transfusion requirement in the intensive care unit were predictive for NOM failure.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the risk of failure with NOM is increased and

Extra vigilance is warranted during non-operative management of patients with trauma to both liver and spleen

extra vigilance is therefore warranted when choosing this form of therapy in the presence of injury to both organs [24]. In a retrospective protocol-driven study performed by Hsieh et al., a failure rate of 4.9% was described [25]. Other parameters that might be helpful in predicting the failure of NOM are lactate

lactate

levels on admission, necessity of transfusion, crystalloid resuscitation

crystalloid resuscitation

and drop-in haematocrit

haematocrit

levels during the first hour after admission [26].…”
Section: Success and Failure Of Non-operative Managementmentioning
confidence: 99%